Saponin Content Analysis on Leaves and Petioles of Carica pubescens Lenne & K. Koch - Minarno, Eko Budi; Laily, Ainun Nikmati; Alfiah, Ida (Proceedings of the International Conference on Green Technology, 2017)
Carica pubescens is a tropical species that adapt to the plateau environment and low temperatures. Morphological, chemical content, and analysis of protein banding pattern on C. pubescens has been done, but more on the analysis of active compounds for pharmaceutical raw materials and its accumulation in the body of the plant has not been widely studied. This study aims to determine the content of saponin in leaf and petiole of C. pubescens in terms of absorbance values. The results showed that the leaf and petiole of C. pubescens positive for the saponins with the formation of stable foam for 60 seconds at 1.5 cm - 1.7 cm. The third positive samples containing saponins triterpene the ring test produces a brownish color. Isolation saponin by TLC shows the best ratio of eluent chloroform:methanol:water (14:6:1) compounds can be separated perfectly. Saponin absorbance values obtained two samples from Cangar area as follows: petiole samples amounted to 0.852 and leaf samples amounted to 0.686. The highest saponins found in organs petiole. Thus the petiole of C. pubescens has the potential to be used as a source of triterpene saponins which can be developed into a commercial herbal medicines.